Peningkatan Efisiensi Transaksi Digital Pada Usaha Mikro Di Desa Tambakbaya - Asep Deddy Supriatna; Hisyam Eka Pramudita; Ai Nur Azizah; Siti Komalasari; Rifki Ahmad Dzulfikri; Faiz Pratama; Vito Gunawan; Bubu Bukhori Muslim; Muhamad Chikal Ubaidilah Nurhasan; M. Gilar Fatih Nurohman; Windi Setia Lestari; Rizki Abdul Hadi; Soni Irawan; Kalma Juniya Farid; Siti Fadillah Kamilah; Adam Ramdan; Arsil Muhammad Harits; Bintang Maulida Fazriani A; Dzakwan Fauzan Padlulloh; Muhammad Ilham Dede Saputra; Nazwa Nurazizah; Ai Hilma Khoiriyah; Jujun Munawar; Muhammad Fahmi Faisal (Institut Teknologi Garut, 2026)
Micro-business owners in Tambakbaya Village still face challenges in keeping up with developments in digital payment systems, particularly due to low digital literacy and limited access to technology. This community service program aims to improve the efficiency of micro-business transactions through the implementation of a digital payment system based on the Indonesian Standard Quick Response Code (QRIS). The implementation method consists of three stages: preparation, implementation, and monitoring. The results of the activity show that of the 22 micro-businesses surveyed, 89.9% had never used a digital payment system before. After the socialization, four businesses successfully activated QRIS and began using it in daily transactions. The results of this activity contributed to increasing digital literacy and introducing modern payment systems at the village level, which is expected to be the first step towards sustainable digital economic transformation in rural areas.